Review of the Fund's Income Position for FY2008 and FY2009. (Policy Papers; Policy Paper ;, 2008)
This paper provides the basis for the annual review of the Fund's income position, including a review of the system of special charges. The paper also sets out proposed decisions relating to the Fund's income position for FY 2008 and FY 2009. The review takes account of the recent discussions in the Executive Board on the new income model for the Fund. The paper is structured as follows: Section II reviews the Fund's FY 2008 income position, provides an explanation of key variances from projections, and discusses the impact of restructuring costs on the income position; Section III makes proposals for the disposition of investment income and the General Resources Account (GRA) income position; Section IV outlines updated projections and proposes a margin for the rate of charge for FY 2009; Section V provides an update on the burden sharing mechanism; and Section VI reviews special charges.